Membangun Karakter Bermisi: Menyelaraskan Kurikulum Merdeka Dengan Teologi Misi Kristen - Rajiman Andrianus Sirait; Maria Titik Windarti (Jurnal Silih Asuh : Teologi dan Misi, 2024)
The importance of Christian learning and formation became very significant, especially in the era of an independent curriculum that emphasized character development as the core of education. This process is more than just moral and intellectual formation, but it is a step towards transformation into a "new man" influenced by the Holy Spirit. Involving the values of the Kingdom of God such as love, justice, and peace in the building of Christian character is important. An independent curriculum provides an opportunity to unify Christian character building by rooting the values of the Kingdom of God, forming customs that support mission, and developing character that reflects Christ. The importance of Christian character-building in education must not be overlooked, for it forms not only extraordinary individuals, but also individuals who are ready to be God's instruments in the realization of His mission in the world..